Ambiente institucional no crédito rural :avanços e retrocessos - Costa, Fernando Bastos (2005)
This work aims to study the institucional environment for the implementation of financing policies directed to familiar agriculture. The central hypothesis is that, although all changes occured in the credit norms, in order to reduce the existing obstacles for the access of outsiders, the same institucional arrangement remains which gave support to the modernization - crystallizer of strengthening structures of this exclusion. The most relevant pressuposition is that the poor agriculturists are the most displayed to the institucional limitations. The concepts of institucional arrangements and environments used in this work had been constructed with support of the institucional school, contemplating itself the economic dimension, the organizational sociology and political science. In the relation of the institucional changes with the state performance, the theorist reading was important that reflect on the relative autonomy of the State and studious of the Brazilian State. The empirical part consisted of a research which had been applied questionnaires with benefited and non-benefited agriculturists with PRONAF B, in thirteen cities of Rio Grande do Norte. In each city, interviews with four of its main mediators had been carried out. The research results had ratified the hypothesis of the work of that the conception of the public policies does not take in account the institution role in the behavior and the choices of the individual and collective agents, inferring itself that this policy, as others, lacks of mediation that exceed the rationality of legal landmarks